Physical disuse contributes to widespread chronic mechanical hyperalgesia, tactile allodynia, and cold allodynia through neurogenic inflammation and spino-parabrachio-amygdaloid pathway activation. Issue 8 (August 2020) - Ohmichi, Yusuke; Ohmichi, Mika; Tashima, Ryoichi; Osuka, Koji; Fukushige, Kaori; Kanikowska, Dominika; Fukazawa, Yugo; Yawo, Hiromu; Tsuda, Makoto; Naito, Munekazu; Nakano, Takashi
Abstract : Abstract: Physical disuse could lead to a state of chronic pain typified by complex regional pain syndrome type I due to fear of pain through movement (kinesiophobia) or inappropriate resting procedures. However, the mechanisms by which physical disuse is associated with acute/chronic pain and other pathological signs remain unresolved. We have previously reported that inflammatory signs, contractures, disuse muscle atrophy, spontaneous pain-like behaviors, and chronic widespread mechanical hyperalgesia based on central plasticity occurred after 2 weeks of cast immobilization in chronic post-cast pain (CPCP) rat model. In this study, we also demonstrated dystrophy-like changes, both peripheral nociceptive signals and activation of the central pain pathway in CPCP rats. This was done by the following methods: (1) vascular permeability (Evans blue dye) and inflammatory- and oxidative stress-related messenger RNA changes (real-time quantitative polymerase chain reaction); (2) immunofluorescence of pERK and/or c-Fos expression in the spino-parabrachio-amygdaloid pathway; and (3) blockade of nociceptive-related signals using sciatic nerve block. Furthermore, we demonstrated tactile allodynia using an optogenetic method in a transgenic rat line (W-TChR2V4), cold allodynia using the acetone test, and activation of dorsal horn neurons in the chronic phase associated with chronic mechanical hyperalgesia using c-Fos immunofluorescence. In addition, we showed that nociceptive signals in the acute phase are involved in chronic pathological pain-like behaviors by studying the effects of sciatic nerve block. Thus, we conclude that physical disuse contributes to dystrophy-like changes, spontaneous pain-like behavior, and chronic widespread pathological pain-like behaviors in CPCP rats after 2 weeks of cast immobilization. Abstract : Supplemental Digital Content is Available in the Text.